RAGAM BAHASA HORMAT KEIGO YANG MENCERMINKAN NILAI UCHI-SOTO-YOSO - Dewi Saparina Halibanon; Selly Nursyamsiah (Jurnal Sastra - Studi Ilmiah Sastra, 2023)
This research title is“Keigo Honorific Language Related to the Concept of Uchi-Soto-Yoso (Sosiolinguistic Studies)”, scientific paper for Japanese literature study program, literature faculty of Universitas Nasional PASIM. This research discusses keigo honorific language related to the concept of uchi-soto-yoso in Nihon Chinbotsu: Kibo no Hito and saiai dramas. Japan has a group-oriented society consisting of uchi, soto, and yoso. This can be seen from the language used, for example language variations such as keigo.The method used in this research is qualitative descriptive, and the data collection technique is taking note method. This research uses sociolinguistic studies to analyze the social factors and language variations that influence the use of keigo.In the results of the analysis, 43 words were found that used the keigo in the form of 9 sonkeigo data, 18 kenjougo data and 16 teineigo data. 12 data were based on social relationships, uchi has 5 data, soto has 4 data, and yoso has 3 data. Social factors that affect keigo are age, social relationships, social status, intimacy, gender and group membership.